Factors contributing to nonadherence to oral hypoglycemic medications among ambulatory type 2 diabetes patients in Southwestern Nigeria - Adisa R; Alutundu MB; Fakeye TO (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
Objective: The overall goal of the study was to evaluate the probable reasons for patients' nonadherence to prescribed oral hypoglycemic medications in an ambulatory care setting in Nigeria with a view to identifying points for necessary intervention to improve adherence and treatment outcomes. Also, the recommended non-drug management options for diabetes patients with emphasis on self monitoring of blood glucose were assessed.Methods: A cross-sectional study was conducted at a 200-bed secondary health care facility in Southwestern Nigeria between 2nd April and 31st May 2008. Copies of pre-tested questionnaire were administered directly to 121 ambulatory patients with type 2 diabetes at the study site. Information on socio-demographic characteristic, probable barriers that affect adherence to prescribed oral hypoglycemic medications, non-drug treatment options for diabetes, and patients' self management efforts were obtained. Descriptive and chi-square statistics were used to evaluate the distribution of respondents' opinion.Results: The response rate was almost 100%. The commonly cited intentional nonadherence practice included dose omission (70.2%). Almost 50% respondents were fed up with daily ingestion of drugs and 19.8% were inconvenienced with taking medications outside home and gave these as reasons for the dose omission. Forgetfulness (49.6%) and high cost of medication (35.5%) were mentioned as major non-intentional reasons for nonadherence. Aside oral medications, 82.6% and 95.0% of respondents respectively, reported moderate exercise and dietary restrictions as part of the prescribed treatment modalities. More than two third of respondents (81.8%) had never monitored blood glucose by themselves. Significant association exist between sex, occupation and patients' tendencies to forget doses of prescribed oral medications (p<0.05). Conclusion: Nonadherence behaviors among ambulatory patients with type 2 diabetes occur mostly, as omission and forgetfulness of doses of medication. Efforts are needed to increase the medication adherence and self management practices of these patients in Nigeria so they can realize the full benefits of prescribed therapies.